Kleine Levin Syndrome: A Rare Neuropsychiatric Disorder - Natan Gadoth (Medical Science: Trends and Innovations Vol. 5, 2025)
Aims: The aim of this chapter is to describe in some detail the evolving concept that Kleine Levin syndrome (KLS), is a neuropsychiatric disorder rather than a rare periodic sleep syndrome. Methodology: A literature search for papers describing psychiatric features in patients with classical KLS as well as Atypical KLS was performed and the psychiatric characteristics of the cases described were divided into those noted before the onset of KLS typical sleep attacks, those noted during attacks and de-novo psychiatric morbidity emerging after a long remission from sleepiness attacks. Results: Psychiatric morbidity is an essential part of KLS besides the classical repeated sleepiness attacks. Its presence significantly contributes to the impaired life quality of the affected youngsters during their prime time of life as well as their families. Moreover, the presence of psychiatric morbidity may significantly delay the diagnosis of KLS. Recent data suggests that psychiatric morbidity in KLS, in particular bipolar disorder, may be linked to early-life morbid events. Conclusion: Awareness of the role of psychiatric morbidity as an associated feature of a rare sleep disorder may shorten the time to definite diagnosis of KLS, avoid unnecessary tests and sometimes, prolonged hospitalizations in psychiatric institutes.